Access and adherence to isoniazid preventive therapy and occurrence of active TB in a cohort of people living with HIV: a retrospective cohort study in Sao Paulo, Brazil - Picone, Camila Melo; Freitas, Angela Carvalho; Gutierrez, Eliana B.; Avelino-Silva, Vivian Iida (Revista do Instituto de Medicina Tropical de São Paulo, 2020)
Tuberculosis (TB) is still a leading cause of morbidity and mortality among people living with HIV (PLHIV). The diagnosis of latent TB is required for the implementation of prophylactic therapy with isoniazid (PTI). However, low access to diagnosis of latent TB and non-adherence to PTI may hinder potential benefits of this essential intervention. In this study, we addressed the access and adherence to PTI in a cohort of PLHIV with positive tuberculin skin test (TST) in a reference HIV clinic in Sao Paulo, Brazil. We have also analyzed the occurrence of active TB over a median of 131 months after a positive TST among study participants. Our findings revealed that 88.3% of the 238 TST-positive patients had access to PTI, and 196 (93.3%) of those with access adhered to PTI. Active tuberculosis was diagnosed in three of the 196 TST-positive patients who adhered to PTI (1.5%; 95% confidence interval [CI] 0.3-4.4%), whereas seven cases were detected among 42 patients without access or who did not adhere to PTI (16.6%; 95% CI 7.0-31.3%). The apparent beneficial effect of PTI in our cohort is consistent with previous studies including PLHIV, and highlights the importance of reliably delivering each of the steps between screening for latent TB and provision of PTI.